Disclosure Practices of Foreign Companies Interacting with U.S. Markets - KHANNA, TARUN; PALEPU, KRISHNA G.; SRINIVASAN, SURAJ (Journal of Accounting Research, 2004)
ABSTRACT We analyze the disclosure practices of companies as a function of their interaction with U.S. markets for a group of 794 firms from 24 countries in the Asia‐Pacific and Europe. Our analysis uses the Transparency and Disclosure scores developed recently by Standard & Poor's. These scores rate the disclosure of companies from around the world using U.S. disclosure practices as an implicit benchmark. Results show a positive association between these disclosure scores and a variety of market interaction measures, including U.S. listing, U.S. investment flows, exports to, and operations in the United States. Trade with the United States at the country level, however, has an insignificant relationship with the disclosure scores. Our empirical analysis controls for the previously documented association between disclosure and firm size, performance, and country legal origin. Our results are broadly consistent with the hypothesis that cross‐border economic interactions are associated with similarities in disclosure and governance practices.